The Efficacy of Alendronate in Children with Secondary Osteoporosis - Original Article - Halil Sağlam; Erdal Eren; Esra Deniz Çakır; Evren Özboyacı; Ali Özboyacı; Taner Özgür; Ömer Tarım (Güncel Pediatri)
Introduction: Osteoporosis which is primarily known as an adult disease may be encountered secondarily due to chronic diseases in children. Biphosphonates can be safely used in treatment with proven benefits. Alendronate is often preferred because of its advantage of oral use. Here, the efficiency and safety of alendronate in children with secondary osteoporosis were evaluated. Materials and Method: A total of 46 children (28 boys; 60.9% and 18 girls; 39.1%) with secondary osteoporosis were included. Alendronate was given orally at a dose of 5 mg once daily for children less than 30 kg and 10 mg once daily for those weighing 30 kg or more. Bone mineral density (BMD) was evaluated with DEXA taken at baseline, at 6th month, at 12th month and at 24th month. Results: Mean standard deviation scores (SDS) of height, weight and body mass index were -2.43, -2.82 and -1.72, respectively. Serum Ca, P and ALP levels were all normal. Mean BMD SDS at baseline, 6th month, 12th month and 24th month were -4.03±0.96 -3.51±1.02, -2.82±1.09 and -2.43±0.93, respectively. Improvements in BMD z-scores at 6th, 12th and 24th months compared to baseline were all statistically significant.Conclusion: Our results showed that oral alendronate treatment which is more comfortable and cheaper than parenteral ones results in significant improvements in BMD, can be safely used and easily tolerated in children with secondary osteoporosis, as in adults. Though a plenty of studies were performed in children, there is still no consensus on the preferred and safe dose of the drug and the duration of treatment, as well as from the beginning of what age can the drug be introduced to the children requiring osteoporosis treatment. (Journal of Current Pediatrics 2010; 8: 86-9)